2017
DOI: 10.3389/fmed.2017.00187
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Expression of the CLOCK Gene in Obstructive Sleep Apnea Syndrome Patients Are Not Reverted by Continuous Positive Airway Pressure Treatment

Abstract: PurposeMetabolic syndrome and cardiovascular disease are strongly associated with obstructive sleep apnea syndrome (OSAS), which causes substantial changes to normal circadian physiological functions, including metabolic pathways. Because core clock genes are known to be modulated by sleep/vigilance cycles, we asked whether the expression level of mRNA coding for clock genes is altered in non-treated OSAS patients and if it can be corrected by standard continuous positive airway pressure (CPAP) treatment.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…Consistent with our current study, the expression of clock genes has been shown to be altered in patients with OSA [19,25]. Moreira et al further revealed that the altered expression of CLOCK gene in seven patients with OSA was not reverted by continuous positive airway pressure (CPAP) treatment [25]. In contrast, Burioka et al demonstrated that the PER1 expression elevated at 02:00 in patients with OSA was significantly decreased by CPAP treatment [19].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our current study, the expression of clock genes has been shown to be altered in patients with OSA [19,25]. Moreira et al further revealed that the altered expression of CLOCK gene in seven patients with OSA was not reverted by continuous positive airway pressure (CPAP) treatment [25]. In contrast, Burioka et al demonstrated that the PER1 expression elevated at 02:00 in patients with OSA was significantly decreased by CPAP treatment [19].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, and following this bidirectional pattern, it is plausible to think that the treatment of nocturnal hypoxemia with CPAP can partially restore the impaired hypoxic pathways and improve the clock genes transcription. However, Moreira et al failed to find improvement in CLOCK expression with CPAP treatment in 17 men with severe SAHOS without type 2 diabetes [34]. This result could suggest that other mechanisms beyond hypoxia and hyperglycemia are involved in the complex regulation of the clock gene system.…”
Section: Discussionmentioning
confidence: 99%
“…However, Moreira et al . failed to find improvement in CLOCK expression with CPAP treatment in 17 men with severe SAHOS without type 2 diabetes [ 34 ]. This result could suggest that other mechanisms beyond hypoxia and hyperglycemia are involved in the complex regulation of the clock gene system.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in expression of clock genes are reported in peripheral blood cells from patients with OSA ( Yang et al, 2019 ). These changes in expression in blood cells are not affected by CPAP treatment ( Moreira et al, 2017 ), suggesting that they persist despite treatment. It is known that the circadian clock in alveolar epithelial cells impacts pulmonary physiology, and its disruption can contribute to disease in animal models ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%